Roda de leitura: gêneros discursivos minicontos e poemas - Peletti, Elisangela Nunes dos Santos (2019)
This study aims at presenting the results of a teaching and research project developed at the Post-Graduation Program - Professional Master's in Letters/PROFLETRAS, whose main purpose was, due to the recorded difficulties at the studied school regarding reading stimulus, to prepare and apply activities, focusing on discursive genres, short stories and poems, that stimulated the reading practice of students from a 8th year of Elementary School; to plan, with the students, activities that could help on developing the joy for reading and that allowed a better achievement of such practice; as well as to develop, with the students, reading circles in different spots of the school. At the end of this project, a soirée was organized with the class for the school community, with the proposed discursive genres. The study was developed with students from a state public school, in Cascavel city, 2018. The main idea of this project was a reading enjoyment proposal (GERALDI, 2011). Thus, the methodological referrals were based on a reading perspective without formal evaluation, since one of the students’ greatest complaints is about the accomplishment of activities for traditional evaluation purposes, after text readings regarding literary area. The theoretical-methodological approach of this study was substantiated on a qualitative/ethnographic research, also according to action-research guidelines (THIOLLENT, 1997), associated to the perspective of multi-literacies (ROJO, 2012). In order to develop a Multi-literacy Project, this research aimed at developing activities that focused on reading practices and also covered the multiplicity of students' cultures and semioses that constitute the texts. So, the available resources by technologies were applied, such as mobile phones and internet to seek for some relation between the school activities and the social practices of students. This study was based, among others, in: Lajolo (1997), Kleiman (2005), Rojo (2012) and Bortoni-Ricardo (2013). The activities, which were mainly based on poems and short stories reading, also included DTIC (Digital Technologies of Information and Communication). Oral activities were still preferential, since they were constituted as goals of this study; and the most important part of this project was the soirée presentation for the school community.